The AI Frontline: Revolutionizing Antibiotic Stewardship and the Fight Against Antimicrobial Resistance - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
— meta_description: Explore how Artificial Intelligence AI is transforming the global fight against Antimicrobial Resistance AMR through enhanced antibioti...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Patient Care